Intracranial Infection Caused by Multidrug-resistant Acinetobacter Baumannii - He, Haiyong; Li, Manting; Guo, Ying; Luo, Lun; Bhattarai, Robin; Li, Wensheng (Nepal Journal of Neuroscience, 2021)
Objective: To report the successful treatment of a patient who underwent vestibular schwannoma resection and developed intracranial infection caused by multidrug-resistant Acinetobacter baumannii (MRAB), and to review the recent relevant literature.Methods: The patient was diagnosed with MRAB infection based on clinical manifestations and cerebrospinal fluid (CSF) culture. The treatment included external ventricular drainage, posterior fossa decompressive craniectomy, and endoscopic lavage for fourth ventricle, subdural drainage, and intravenous injection /ventricular irrigation of sulperazone.Results: The MRAB-induced intracranial infection was successfully cured. The follow-up lasted for 84 months, and the patient has resumed normal life and work.Conclusion: Active individualized treatment should be administered at the earliest. The drainage of CSF, ventricular lavage, and proper choice of antibiotics are key to treat intracranial infections caused by MRAB.